Disentangling the effects of sex and gender on APOE ɛ4–related neurocognitive impairment - Tatiana Dessy; Amina Barhdadi; Marie‐Christyne Cyr; Johanna Sandoval; Louis Bherer; Joëlle Rouleau; Sylvie Provost; Louis‐Philippe Lemieux Perreault; Marie‐Pierre Sylvestre; Sarah A. Gagliano Taliun; Marie‐Pierre Dubé (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring)
Abstract INTRODUCTION The apolipoprotein E (APOE) ɛ4 allele is a well‐established risk factor for neurocognitive impairment (NCI), with varying impacts between men and women. This study investigates the distinct roles of sex and gender in modifying APOE ɛ4–related NCI. METHODS Biological sex was inferred from sex chromosomes, and a femininity score (FS) was used as a proxy for gender. We analyzed 276,596 UK Biobank participants without prior NCI to assess whether sex and FS modified the effect of APOE ɛ4 on NCI. RESULTS NCI risk was higher in APOE ɛ4 carriers compared to non‐carriers (hazard ratio [HR] = 2.48 in females; HR = 1.96 in males) with significant interaction by sex (P < 0.0001). FS was associated with an increased NCI risk after accounting for sex (HR = 1.07, 95% confidence interval: 1.04–1.10, P < 0.0001) with no significant differences by sex or APOE ɛ4 carrier status. DISCUSSION Our findings show that APOE ɛ4 increases NCI risk more in females, while FS independently elevates risk across sexes. Highlights Apolipoprotein E (APOE) ɛ4 increases neurocognitive impairment (NCI) risk, with a greater impact in females (hazard ratio [HR] = 2.48) than males (HR = 1.96). Sex significantly modifies the effect of APOE ɛ4 on NCI (P < 0.0001f). Femininity score increases NCI risk (HR = 1.07) independently of sex and APOE ɛ4. Understanding the distinct sex and gender contributions to APOE ɛ4–related NCI can improve interventions.